“Ulner Bone Graft For Nasal Reconstruction” - R. N. Sharma (Indian Journal of Plastic Surgery)
Four patients undergoing nasal skeletal reconstruction with ulner bone graft are reviewed. The rationale for the use of ulner bone graft is discussed and it is observed that ulner hone grafts give better results in reconstructing the skeletal defects of the nose.